Kewenangan Notaris dalam Pembuatan/ Pencabutan Surat Wasiat (Testament) - Agus Wahyu Suniayasa; I Nyoman Sumardika; Ni Gusti Ketut Sri Astiti (Jurnal Preferensi Hukum, 2020)
Humans are social creatures which in their lives always need help from those around them even though that person is about to die. Therefore, a person while away from death has the desire to arrange an inheritance which may be passed on to his offspring. After a person passed away, this wealth can cause problems in the family and society. So rules and solutions are needed according to applicable and permanent laws which refer to the appropriate Law. For example, if someone's message is to be revealed, it can be written into an authentic will deed made by a notary public which is commonly called a will or testament. This study aimed to reveal how the authority of the notary in making a will or testament and how the duties and authority of the notary in the event of execution of wills or if there is revocation of wills. This research employed a normative method and is studied with a statutory approach and a conceptual approach. The legal materials used are primary and secondary legal materials, which are processed and analyzed descriptively. The results of this study indicated that the notary has the authority to keep a will as a written or closed will and is entitled and obliged to report the will to Balai Harta Peninggalan in the area where the notary serves. In addition, if the testator changes the contents of his will, the notary must report the matter to the Central Register of Wills.